Ferroptosis as a Biological Phase Transition III: Ephitelial-Mesenchymal Transition - Suárez-Ogando, H.; Guerra, A.; Mansilla, R.; Nieto-Villar, J.M. (Discontinuity, Nonlinearity, and Complexity, 2026)
In the present work, a model is proposed where the ferroptosis process is related to the stages of avascular and vascular tumor growth, including the process of epithelial-mesenchymal transition. It was found that the ferroptosis process induces cell death more effectively in cells with a mesenchymal phenotype. Furthermore, it was observed that for certain compositions of epithelial and mesenchymal cells the tumor growth system exhibits less complexity. From the evaluation of the entropy production rate, it was identified that an increase in the concentration of oxidized lipid peroxide species generates an increase in the robustness of the ferroptosis process, while decreasing the robustness of the epithelial-mesenchymal transition mechanism.